The role of leptin in monitoring training loads during rowing: a systematic review - Mardyla, M.; Grandys, M. (Journal of Kinesiology and Exercise Sciences, 2021)
Objective: In competitive sports, too small or too large loads lead to poor sports results. Situation of overload are particularly dangerous to the body, which may lead to overtraining. In this work, the literature on the possibility of assessing training loads with the use of leptin concentration measurement in men and women practicing rowing was analysed. Materials and methods: A systematic review was performed using the Scopus, Pubmed and Google Scholar databases between 1995-2020. After an initial analysis of 56 articles and taking the analysed topics into account, 25 articles were included in this review. As part of the review, data for 75 rowers were analysed. The usefulness of leptin - a hormone produced by adipose tissue - as a marker of training loads in several sports disciplines, with particular emphasis on rowing, was evaluated. Within this context, the role of leptin may be to control these loads due to its relatively high sensitivity in response to increases in training intensity or volume. The presented general characteristics of rowing and the physiological basis of exercise are the background for considerations on the possibility of using leptin as a burden marker in this discipline. Results: Due to the fact that the concentration of leptin correlates with the content of adipose tissue and BMI (Body Mass Index), its changes may inform about training loads directly related to the amount of energy expenditure. A review of the literature from the last 25 years, i.e. from the moment when this hormone was discovered, allowed to formulate the thesis that leptin may be a marker of training loads, however, determining its concentration makes sense when the same factors that may affect its secretion are taken into account each time. Conclusions: Training in rowing, that involves high training loads, causes significant changes in blood leptin levels. Training periods with high exercise load, associated with a significant increase in energy expenditure, lead to a decrease in resting leptin concentration, while periods with less load increase it. The main factor determining changes in leptin concentration during training is the amount of energy expenditure, which in the case of rowing involving very large muscle groups, is very high. Although the amount of energy expenditure in training, leading to a decrease in leptin concentration is difficult to determine, the energy expenditure cannot be less than 800 kcal in a single training unit.